O Brasil visto de cima: o campo de uma periferia a partir de centros de produção etnigráfica - Chaves, Estêvão Barros (2018)
This thesis intends to observe the relationship between brazilian and foreign anthropologies, seeking the representation among it in the many senses that they may acquire. From the double “center-periphery” relations - between anthropologists and natives on one side, and central and marginal anthropologies on another- the research will seek to highlight the ways in which relations are established and their contents. In this sense, it will be necessary to see, among other elements, how certain "central" anthropologies dialogue with the Brazilian anthropology when its objects are in Brazil, At another level, we will look for definitions on the Brazilian anthropology in instruments such as encyclopedias, dictionaries and, mainly, periodicals. At this point, we intend to compare "outsiders" and "internal" views, produced, however, for a global audience, as a mechanism for observing the type of relationships that can be understood within vectors conceived by the "center-periphery" axis. How then could we observe the multiple positions that Brazilian anthropology occupies in the international field? The idea, therefore, is to build a typology of relationships that helps to think certain international politics about Brazilian anthropology.